Neželeni dogodki v zdravstvenem okolju na Univerzitetnem rehabilitacijskem inštitutu Republike Slovenije - Soča v letih od 2007 do 2011 - Zupančič Knavs, Irena (Rehabilitacija (Ljubljana), 2013)
Background: The article explains what an incident in health care environmentis, how to act when it happens, and how to prevent incidents. The empirical part addresses incidence of injuries with contaminated sharp objects at the University Rehabilitation Institute in Ljubljana between 2007 and 2011. Based on the filed injury-at-work reports we wanted to assess the frequency and type of incidents as well as the types of injured health care professionals. In addition, we wanted to investigate the protection of the injured persons against hepatitis B virus (HBV) based on the data on serological blood tests. Methods: The data on the incidents were acquired from the filled-in reports on injuries at work of health care professionals. In addition, in 2008, a questionnaire was introduced for all those involved in the incidents containing the question whether the person had been vaccinated against HBV(and if so, when). Descriptive statistics were used for data analysis. Results: During the study period 41 incidents occurred. The majority of the injuries (80%) were caused by used needle. The incidents mainly involved nurses (32 cases); physicians (3 cases), hospital attendants (3 cases) and cleaning ladies (3 cases) were less frequently involved. Serological blood tests following the incidents revealed that among the 33 injured who had been vaccinated against HBV, as many as 13 (40%) had no HBV antibodies in their blood and were hence re-vaccinated. Conclusion: Our Institute has established precise rules of action upon injuries at work. The staffs are reminded of those procedures through our hospital infection prevention programme, as well as through lectures on incidents and their prevention. Any work-related injury, and especially an incident, should be immediately reported so that adequate action can be taken if necessary.
Keywords: health care professionals; Health personnel; ostri predmeti; poškodbe; poškodbe pri delu; sharp objects; work-related injuries; zdravstveni delavci